Conduct of Clinical Trials: Asia Pacific Region Versus Global - Ambade, Mrunal (IJRDO-Journal of Applied Science, 2018)
Conducting clinical trials , this process is time-consuming and complicated, which required substantial investment. Pharmaceutical and biotechnology companies and in the Europe and United States (US) face escalating clinical trial challenges and cost in both retaining and recruiting patients. Additionally, sponsor pharmaceutical companies have to face complex regulation and continuously evolving regulatory processes. Due to these complication and, US and European biotechnology and pharmaceutical companies outsource their clinical studies to Asia pacific region. This article draw a special attention to the research on increasing trend in conducting clinical trials in Asia pacific region and worldwide.